Implementasi Nilai-Nilai Filsafat Progresivisme dalam Kurikulum Merdeka - Eka Prawidianto (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research was conducted to examine the relationship between the values ​​of the philosophy of progressivism and its implementation in the Independent Curriculum, which is currently the direction of educational reform in Indonesia. The background of the research stems from the need to understand the philosophical foundations that underpin the new curriculum policy, especially since the Independent Curriculum emphasizes flexible, contextual, and learner-centered learning. The purpose of this research is to identify relevant principles of progressivism and explain how these principles are integrated into the established curriculum structure, pedagogy, and learning practices. The method used is a literature study by reviewing various scientific articles, books, and official documents that discuss progressivism and the Independent Curriculum, then organizing the findings through content analysis to see patterns and conceptual relationships between the two. The results of the study indicate that the Independent Curriculum has a strong alignment with progressivism, especially in aspects of experience-based learning, learning differentiation, character development, and repositioning the role of teachers as facilitators. The study's conclusions confirm that the Independent Curriculum is not only a policy innovation but also a direct implementation of a progressive education paradigm that encourages independence, creativity, and holistic student development. These findings provide a philosophical basis for strengthening the implementation of the Independent Curriculum and also open up space for further research related to the application of progressivism in learning practices across various educational contexts.